Interpretation of autoantibody positivity in interstitial lung disease and lung-dominant connective tissue disease - Pereira,Daniel Antunes Silva (2013)
The initial evaluation of patients with interstitial lung disease (ILD) primarily involves a comprehensive, active search for the cause. Autoantibody assays, which can suggest the presence of a rheumatic disease, are routinely performed at various referral centers. When interstitial lung involvement is the condition that allows the definitive diagnosis of connective tissue disease and the classical criteria are met, there is little debate. However, there is still debate regarding the significance, relevance, specificity, and pathophysiological role of autoimmunity in patients with predominant pulmonary involvement and only mild symptoms or formes frustes of connective tissue disease. The purpose of this article was to review the current knowledge of autoantibody positivity and to discuss its possible interpretations in patients with ILD and without clear etiologic associations, as well as to enhance the understanding of the natural history of an allegedly new disease and to describe the possible prognostic implications. We also discuss the proposition of a new term to be used in the classification of ILDs: lung-dominant connective tissue disease.